2018
DOI: 10.1016/j.yjmcc.2018.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Sestrin2 prevents age-related intolerance to post myocardial infarction via AMPK/PGC-1α pathway

Abstract: We have revealed that a novel stress-inducible protein, Sestrin2, declines in the heart with aging. Moreover, there is an interaction between Sestrin2 and energy sensor AMPK in the heart in response to ischemic stress. The objective of this study is to determine whether Sestrin2-AMPK complex modulates PGC-1α in the heart and protects the heart from ischemic insults. In order to characterize the role of cardiac Sestrin2-AMPK signaling cascade in aging, C57BL/6 wild type young mice (3–4 months), aged mice (24–26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 32 publications
2
60
0
Order By: Relevance
“…We found that Sestrin2 prevents age-related intolerance to ischemia and reperfusion injury by modulating substrate metabolism. These findings further confirm that Sesn2 is a potential target that could prevent age-related susceptibility to ischemic heart disease [105,106].…”
Section: Sesn2 and Ischemic Heart Diseasesupporting
confidence: 76%
“…We found that Sestrin2 prevents age-related intolerance to ischemia and reperfusion injury by modulating substrate metabolism. These findings further confirm that Sesn2 is a potential target that could prevent age-related susceptibility to ischemic heart disease [105,106].…”
Section: Sesn2 and Ischemic Heart Diseasesupporting
confidence: 76%
“…As a stress-inducible metabolic regulator, sesn2 has been proven to protect the mitochondria from oxidative damage both in vivo and in vitro (32,33). To clarify the potential association between sesn2 and AMPK, the expression of these two molecules was determined in diabetic rats ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…et al, 2017 ). On the other hand, AMPK has been widely known involved in coordinating a series pathophysiological responses under ischemic stress, and pharmacological activation of AMPK has been found preventing inflammation and cellular death, reducing cardiac remodeling post-myocardial infarction ( Calvert et al, 2008 ; Peairs et al, 2009 ; Chiang et al, 2017 ; Kim et al, 2017 ; Quan et al, 2018 ). In our study, we found that SH treatment elevated the activation of AMPK on post-infarct heart and post-hypoxia H9C2.…”
Section: Discussionmentioning
confidence: 99%
“…Adenosine monophosphate-activated protein kinase (AMPK), which consisted of three subunits, α, β, γ, that together made a functional enzyme, worked as an energy sensor to provide metabolic adaptations under the ATP-deprived conditions, such as ischemia and nutritional stress ( Calvert et al, 2008 ; Quan et al, 2018 ). Activation of AMPK has been confirmed exerting pleiotropic functions against inflammatory response and tissue fibrosis and owning beneficial properties in a series of diseases ( Peairs et al, 2009 ; Chiang et al, 2017 ; Kim et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%